Effect of Refined Nursing on Wound Complications After Thoracoscopic Surgery for Lung Cancer - Yanxia Dong; Guangqin Ma; Shuaishuai Wu; Shuling Zhang (The Clinical Respiratory Journal)
ABSTRACT Introduction Lung cancer thoracoscopic postoperative wound complications bring great pain and inconvenience to patients. Methods To provide clinical nurses with a more scientific and effective nursing plan, this study evaluated the effect of refined nursing on wound complications after thoracoscopic surgery for lung cancer. Two‐hundred thirty patients undergoing thoracoscopic radical resection for lung cancer were randomly divided into two groups according to the random number table method. The study group received refined nursing intervention (115 cases), and the control group received routine nursing intervention (115 cases). The effects of the two groups' nursing modes on the wound complications (pleural effusion, incision infection, lung leakage, and wound bleeding) after thoracoscopic surgery for lung cancer were compared. Results According to the study results, the study group experienced a shorter intraoperative blood loss, lower extubation time, shorter hospital stay, and lower wound complication rate than the control group (p < 0.05). Compared to the control group, the study group had significantly lower Hamilton Anxiety Scale (HAMA), Hamilton Depression Scale (HAMD) and visual analog scale (VAS) scores, and higher the short form 36 health survey questionnaire (SF‐36) scores (p < 0.05). Conclusion Compared with the control group, the implementation of refined nursing intervention for patients with thoracoscopic radical resection of lung cancer has fewer postoperative wound complications and can improve patients' nursing satisfaction and quality of life, which is worthy of clinical promotion and application.